Comparative Analysis of Legal and Institutional Frameworks on Labour in Uganda and USA and Their Implications on Workers Rights - Mildren Philomena Awor (Uganda Christian University, 2025)
This research examines the legal and institutional frameworks on Labour in Uganda and the USA, with an analysis on their impact on workers’ rights. The researcher thus adopted a desktop research method and to come at conclusive findings. The study was guided by both general and specific objectives which among others include to analyze the theoretical frameworks on labour rights protection, to explore the international labour standards and best practices on the protecting of workers rights, to analyze Uganda’s legal and institutional frameworks on labour rights protection in comparison with USA labour protections standards This study scores that both countries much as their development trends are not at the same pace, they have legal and institutional system in place that help in governing the workers and their rights such as protection against discrimination based on factors such race, sex, color name it, regulation of working hours and leave both countries have laws that regulate minimum wage although the specifics differ. The study delves further into the existing mechanisms on the protection of workers’ rights at the place of work. And the mechanisms for resolution of dispute which in both countries include industrial courts in Uganda and the Equal Opportunity Commission (EEOC) and courts in the USA which is a more developed system of labour law enforcement than that of Uganda which is still developing. The Researcher concludes that much as both countries do have a functional legal and institutional framework and possesses numerous strengths, they do have weaknesses in their Labour laws and regulations and as provided possible recommendations which include Uganda strengthening its labour laws especially in the informal sector, enhancing collective bargaining and worker organization and promoting capacity building on how to better promote fair labour standards and protection of workers’ rights.
Dissertation